Pseudovitamin B12 is the corrinoid produced by Lactobacillus reuteri CRL1098 under anaerobic conditions - Santos, Felipe (2007)
We have reported previously on the ability of Lactobacillus reuteri to produce a compound with vitamin B12 activity. Here we report on the chemical characterisation of this corrinoid-like molecule. High performance liquid chromatography coupled to an ultraviolet diode array detector, mass spectrometry and nuclear magnetic resonance spectroscopy has enabled us to identify the compound as Coα-[α-(7-adenyl)]-Coβ-cyanocobamide or pseudovitamin B12. This molecule differs from cobalamin in the α-ligand, where it has adenine instead of 5,6-dimethylbenzimidazole bound in a α-glycosidic linkage to C-1 of ribose. L. reuteri is the first lactic acid bacterium in which the production of a cobalamin-like molecule has been identified and the first microorganism reported to produce exclusively pseudo-B12. © 2007 Federation of European Biochemical Societies.